Alasan Pelanggaran Maksim Cara/Pelaksanaan dalam Prinsip Kerja Sama Grice pada Budaya Masayarakat Riau - Fatmawati; Rika Ningsih (Medan Resource Center, 2022)
This research is motivated by the existence of a gap between the concept of Grice's cooperative principle and its application in the culture of the Riau people. The problem in this research is what is the reason for the violation of the maxim of manner in the culture of the Riau people? This study uses a qualitative approach with the grounded theory method. Informants in this study amounted to 79 informants who came from a number of districts in Riau and Riau Islands. The data analysis technique in this study consisted of three stages, namely: open coding, axial coding, and selective coding. The conclusion of this research shows that cultural differences make Grice's principle of cooperation, especially the maxim of manner, not universally applicable to all languages. There are a number of reasons for violating the maxim of manner, namely reasons of politeness, confusion in giving answers, forgetting, nervousness, empathy, avoiding direct speech, secrets, substitute vocabulary, pleasantries, pleasantries, lying, habits, and upset/angry. Violation of Grice's cooperative principle is not a bad thing, in fact the violation occurs because of the cultural influence that exists in the language. The violation of Grice's maxim of cooperation in a language is a manifestation of the actual principle of cooperation in that language.